Combined (endo-)vascular intervention and microsurgical lower extremity free flap reconstruction—A propensity score matching analysis in 5386 ACS-NSQIP patients. Issue 5 (May 2021) - Haug, Valentin; Kadakia, Nikita; Panayi, Adriana C.; Kauke, Martin; Hundeshagen, Gabriel; Diehm, Yannick; Fischer, Sebastian; Hirche, Christoph; Kneser, Ulrich; Pomahac, Bohdan
Summary: Background: Compromised lower limb perfusion due to vascular changes such as peripheral artery disease impedes wound healing and may lead to large-scale tissue defects and lower limb amputation. In such patients with defects and compromised or lacking recipient vessels, combined vascular reconstruction with free flap transfer is an option for lower extremity salvage. Methods: By using the American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database (2005–2018), we analyzed two patient cohorts undergoing (A) free flap lower limb reconstruction (LXTR) only and (B) combined (endo-)vascular reconstruction (vascLXTR). The preoperative variables assessed included demographic data and comorbidities, including smoking, diabetes mellitus, preoperative steroid use, and American Society of Anesthesiology (ASA) Physical Status Classification. Using a neighbor matching algorithm, we performed a 1:1 propensity score matching of 615 LXTR patients and 615 vascLXTR patients. Bivariate analysis for postoperative surgical and medical complications was performed for outcomes in the propensity-matched cohort. Results: We identified 5386 patients who underwent microsurgical free flap reconstruction of the lower extremity. A total of 632 patients underwent a combined (endo-)vascular intervention and lower extremity free flap reconstruction. Diabetes and smoking were more prevalent in this group, with 206 patients having diabetes (32.6%) and 311 being smokers (49.2%). More patients returned to the operating room in the cohort that underwent a combined vascular intervention (24.4% versus 9.9%; p <0.0001). The 30-day mortality for patients undergoing a combined vascular procedure was 3.5%, compared with 1.3% with free tissue transfer only ( p <0.0001). Conclusion: Despite the risks associated, the combined intervention decreases the very high mortality associated with limb amputation in severely sick patient populations. Careful preoperative assessment of modifiable risk factors may reduce complication rates while allowing limb salvage.